Teacher support, entrepreneurial learning, and self-regulated learning predict vocational students’ entrepreneurial intentions - Eliza Eliza; Rino Rino (Global Econedu, 2026)
This study examines the effects of entrepreneurial learning, teacher support, and self-directed learning on the entrepreneurial intentions of vocational students and explores the mediating role of entrepreneurial learning and independent learning. Quantitative causal design was used by involving 303 Class XI students from nine public vocational schools in Pesisir Selatan Regency, Indonesia. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Entrepreneurship learning had the strongest direct effect on entrepreneurial intention (β = 0.497, p < 0.005), followed by teacher support (β = 0.211, p = 0.006). Entrepreneurial learning significantly mediated the relationship between teacher support and entrepreneurial intent (β = 0.339, p < 0.005). Improving teacher support, entrepreneurship education, and self-paced learning is essential to strengthen the entrepreneurial intentions of vocational students